A calcium zirconate based combined material for calcium-copper chemical looping technology. (April 2020) - Westbye, Alexander; Aranda, Asunción; Dietzel, Pascal D.C.; Di Felice, Luca
Highlights: A new combined calcium-copper material based on CaZrO3 . 40 wt% CuO loaded materials at CuO/CaO = 2 and 10 are stable during TGA tests. 50 wt% CuO loaded materials deactivate due to copper migration and agglomeration. Mixed phases (Ca2 CuO3 and CaCu2 O3 ) are not expected to affect material performance. Abstract: Combined calcium-copper materials based on calcium zirconate (CaO/CuO/CaZrO3 ) for Calcium-Copper Chemical Looping (Ca-Cu Looping) have been synthesized using a scalable wet chemical method and characterized by powder X-ray diffraction (PXRD) with Rietveld refinement, temperature-programmed reduction (H2 -TPR) and oxidation (O2 -TPO), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and 45–50 cycles in a thermogravimetric analyser (TGA) representing realistic Ca-Cu Looping conditions. A material at 50 wt% active CuO loading and a CuO/CaO weight ratio of 2 deactivated due to copper migration and agglomeration, while materials with 40 wt% active CuO loading were stable throughout TGA cycles at CuO/CaO ratios of 2 and 10. 40 wt% CuO loaded combined CaO/CuO/CaZrO3 materials are promising candidates for Ca-Cu Looping with a demonstrated tuneable and stable CuO/CaO ratio (≥ 2 [wt/wt]) that could lead to process intensification. The maximum CuO loading for the investigated materials is likely found in the range of [40, 50) wt%, subject to the constraints of Ca-Cu Looping relevant CuO/CaO ratios (≥ 2 [wt/wt]) and the performed TGA testing.